The distribution pattern of suspended solid in a small rubber catchment. - Yusoff, Mohd. Kamil; Awang Soh, Zakaria; Yaziz, Mohd. Ismail (1989)
The study on the distribution pattern of suspended solid was carried out in a small catchment (6.5 hectares) planted with rubber trees. The trees are approximately 15 years old. The discharge from the catchment was measured using a water level recorder and an automatic sampler was used to collect water samples for suspended solid analysis. The water samples were collected for the whole duration of several storm events at 15-minute intervals. Results from the analyses of three storm events showed that the distribution pattern of the suspended solid took the shape of loops. The peak concentration of suspended solid appeared before the peak discharge. The results also demonstrated that surface cover had appreciably influenced the appearance of the suspended solid peak concentrations during a storm event.